SHOULD A VISIT TO THE RADIOLOGY DEPARTMENT BE THE FIRST STEP IN THE DIAGNOSIS OF ACTIVE INFLAMMATORY BOWEL DISEASE?. (8th June 2013) - Cotter, M; Christopher, B; Jadhav, S; Sengupta, S; Keohane, J
Abstract : Introduction: CT is the most commonly used method of imaging in the diagnosis and management of Inflammatory Bowel Disease. However, for those patients admitted with typical symptoms, does imaging accurately identify Crohn's Disease (CD) and Ulcerative Colitis (UC) prior to direct visualisation and histological diagnosis at endoscopy? Aims/Background: To assess the correlation between the findings of contrast CT (abdomen or enteroclysis) and colonoscopy results in patients with a suspected diagnosis of IBD. Method: A retrospective study was performed on 27 patients between September 2009 and January 2013, the majority of whom had been referred for endoscopy to confirm the results of their initial CT. Histopathological results and macroscopic findings at colonoscopy were compared to features of active inflammation as noted on contrast CT. Results: There were 19 female and 8 male subjects. The average age at time of CT was 51 (female) and 32 (male) with a range of 19 to 86 years. The most common clinical indication for performing CT was abdominal pain (74%). Of note, 21 patients had a plain film of abdomen prior to CT, 19 of which were reported normal. Ct enteroclysis was performed on 4 patients. 27 patients had CT findings suggestive of IBD on CT whereas only 17 (63%) had confirmed CD or UC at endoscopy. Conclusion: This study suggests that in a cohort of patients likely to be exposed to high doses of radiation, such as those with IBD, a visit to the endoscopy room could be more worthwhile in their initial diagnosis.